Pupils’ interests in teaching subjects and peculiarities of their memory and thinking - Dževečka, A. (Psichologija, 1983)
The aim of the article is to display individual peculiarities of memory and thinking of two groups of senior pupils. The first group involves pupils interested in exact sciences (mathematics, physics, chemistry). The other group contains pupils interested in humanitarian and art subjects (language, literature, music and other kinds of art). According to the relation between pupils’ interests in teaching subjects and their content, the pupils of each group are divided into subgroups. The article analyses peculiarities of memory and thinking of these subgroups. The author comes to the conclusion that the statement of specific relations between various kinds of interests in teaching subjects and peculiarities of memory and thinking is of great importance for the characterization of pupils’ interests as well as their memory and thinking